In-season assessment of agronomic nitrogen use efficiency and its components in winter wheat using critical nitrogen dilution curve - Li, Bing; Ma, Xiaodong; Zhao, Ben; Wang, Laigang; Ata-Ul-Karim, Syed Tahir (Frontiers in Plant Science, 2023)
Accurate and timely nitrogen (N) scheduling requires the knowledge of in-season crop N deficit. Therefore, understanding the association between crop growth and crop N demand during its growth period is not only imperative for fine-tuning N scheduling decisions to actual crop N demand but also to enhance N use efficiency. The concept of critical N dilution curve has been employed to assess/quantify the intensity and time of crop N deficit. However, the research regarding the association between crop N deficit and N use efficiency in wheat is limited. The present study was carried out to determine whether there are relationships between the accumulated nitrogen deficit (Nand) and agronomic N use efficiency (AEN) as well as with its components (N fertilizer recovery efficiency (REN) and N fertilizer physiological efficiency (PEN)) of winter wheat, and to explore the potential capacity of Nand for predicting AEN and its components. Data acquired from five variable N rates (0, 75, 150, 225, 300 kg ha-1) field experiments using six winter wheat cultivars were used to establish and validate the relationships between Nand and AEN, REN, and PEN. The result indicated that plant N concentration in winter wheat was significantly affected by N application rates. Nand varied from -65.73 to 104.37 kg ha-1 after Feekes 6 stage under different N application rates. The AEN and its components were also affected by the cultivars, N levels, seasons, and growth stages. A positive correlation was observed between Nand and AEN and its components. Validation using an independent data set showed the robustness of the newly developed empirical models to accurately predict AEN, REN, and PEN with an RMSE of 3.43 kg kg-1, 4.22%, and 3.67 kg kg-1 and RRMSE of 17.53%, 12.46%, and 13.17%, respectively. This indicates that Nand has the potential to predict AEN and its components during the growth period of winter wheat. The findings will assist in improving in-season N use efficiency by fine-tuning N scheduling decisions in winter wheat cultivation.